2018
DOI: 10.3390/f9070397
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Small RNA Sequencing Analysis Revealed Roles of PaWB-Related miRNAs and Genes in Paulownia fortunei

Abstract: Paulownia witches' broom (PaWB) is an epidemic disease caused by phytoplasmas infection, which is responsible for large production and economic losses. The study of PaWB has made significant progress, but the specific molecular mechanisms associated with PaWB remain unclear. To clearly know the gene expression profiles of plantlets infected with phytoplasmas, in this study, we used high-throughput sequencing technology to generate an integrated analysis of the transcriptome and microRNAs (miRNAs) of Paulownia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…By comparing the miRNA and transcriptome before and after PaWB, 74 pf-miRNAs targeting 42 PfBTB s were found. We found that PfBTB14 , their target gene, was increased in diseased seedlings, while pf-miRNA159a and pf-miRNA159b-3p were downregulated in diseased seedlings [ 48 ]. Infected seedlings had increased pf-miRNA114 expression, and its PfBTB44 target gene had increased expression as well.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the miRNA and transcriptome before and after PaWB, 74 pf-miRNAs targeting 42 PfBTB s were found. We found that PfBTB14 , their target gene, was increased in diseased seedlings, while pf-miRNA159a and pf-miRNA159b-3p were downregulated in diseased seedlings [ 48 ]. Infected seedlings had increased pf-miRNA114 expression, and its PfBTB44 target gene had increased expression as well.…”
Section: Discussionmentioning
confidence: 99%
“…Many differentially expressed genes (DEGs) among these samples were identified. Studies using the gene ortholog (GO) functional and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway databases indicated that these DEGs are involved in various pathways, including phytohormone biosynthesis, photosynthesis and plant-pathogen interaction [51][52][53][54][55][56][57][58].…”
Section: Transcriptional Responsesmentioning
confidence: 99%
“…Transcriptome analyses from various tree species indicate that the putative role of gene families belonging to receptor kinases, transcription factors, and secondary wall biosynthesis are highly expressed in wood-forming cells [17][18][19][20][21]. At a molecular level, studies related to Paulownia gene expression profiling published in the last few years have primarily focused on drought tolerance and host-pathogen interactions [22][23][24][25]. Cambial development (the initiation and activity of the vascular cambium) leads to an accumulation of wood (secondary xylem tissue).…”
Section: Introductionmentioning
confidence: 99%